SYSTEM DYNAMICS MODELING OF OPTIMIZING GEOTHERMAL POTENTIAL IN INDONESIA TOWARDS EMISSION REDUCTION EFFORT: A CASE STUDY IN STATE-OWNED ENERGY ENTERPRISE - Yudho Aji, Dhamar
The energy sector has an important task to provide fuel for people to operate their businesses and households. On the other hand, the energy sector is also one of the major contributors to Greenhouse Gas (GHG) emissions. The Government of Indonesia has set long-term strategy for transitioning to more low-carbon energy to enhance country’s economic resilience and sustainable development. To realize that strategy, energy sector in Indonesia should implementing energy transition plan by diversifying their portfolios to incorporate renewable energy into their operations to reduce environmental footprint. Indonesia has an abundance of geothermal resources; hence the development of geothermal energy may become one of those phases.